Improving Voluntary, Rights-Based Family Planning: Experience From Nigeria And Uganda - Hardee K; Jurczynska K; Sinai I; Boydell V; Muhwezi DK; Gray K; Wright K (Dove Medical Press, 2019)
Karen Hardee,1 Kaja Jurczynska,2 Irit Sinai,3 Victoria Boydell,4 Diana Kabahuma Muhwezi,5 Kate Gray,6 Kelsey Wright7 1What Works Association, Arlington, VA, USA; 2Palladium, London, UK; 3Palladium, Washington, DC, USA; 4Graduate Institute Geneva, Geneva, Switzerland; 5Reproductive Health Uganda, Kampala, Uganda; 6IPPF, London, UK; 7University of Wisconsin, Madison, WI, USACorrespondence: Karen HardeeWhat Works Association, Arlington, VA, USAEmail Karen.Hardee@hardeeassociates.comBackground: Growing focus on the need for voluntary, rights-based family planning (VRBFP) has drawn attention to the lack of programs that adhere to the range of rights principles. This paper describes two first-of-their-kind interventions in Kaduna State, Nigeria and in Uganda in 2016–2017, accompanied by implementation research based on a conceptual framework that translates internationally agreed rights into family planning programming.Methods: This paper describes the interventions, and profiles lessons learned about VRBFP implementation from both countries, as well as measured outcomes of VRBFP programming from Nigeria.Results: The intervention components in both projects were similar. Both programs built provider and supervisor capacity in VRBFP using comparable curricula; developed facility-level action plans and supported action plan implementation; aimed to increase clients’ rights literacy at the facility using posters and handouts; and established or strengthened health committee structures to support VRBFP. Through the interventions, rights literacy increased, and providers were able to see the benefits of taking a VRBFP approach to serving clients. The importance of ensuring a client focus and supporting clients to make their own family planning choices was reinforced. Providers recognized the importance of treating all clients, regardless of age or marital status, for example, with dignity. Privacy and confidentiality were enhanced. Recognition of what violations of rights are and the need to report and address them through strong accountability systems grew. Many lessons were shared across the two countries, including the need for rights literacy; attention to health systems issues; strong and supportive supervision; and the importance of working at multiple levels. Additionally, some unique lessons emanated from each country experience.Conclusion: The assessed feasibility and benefits of using VRBFP programming and outcome measures in both countries bode well for adoption of this approach in other geographies.Keywords: rights-based family planning, Nigeria, Kaduna State, Uganda